Development of Digital Teaching Materials with a STEM Approach to Atmospheric Dynamics Weather and Climate Submaterials - Tyanka, Zaura Salsalvibilla Putri; Chun, Desmond Tan Chia; Mukti, Anditya Bagus Krisna (CV Bumi Spasial, 2024)
The advancement of 21st-century technology has significantly impacted various fields, particularly education. Teachers are now encouraged to integrate technology into their teaching methodologies. Digital teaching materials enhance the learning process by promoting active and independent learning. This study aims to develop digital teaching materials utilizing a STEM (Science, Technology, Engineering, and Mathematics) approach to support Geography education. Employing the Research and Development method, this research follows the ADDIE model, focusing on the Analysis, Design, and Development phases to create valid and feasible digital teaching materials, as evaluated by expert validators. Validation was performed by media and material experts, a linguist, and a Geography teacher, involving 36 students from class 10 IPS 2 at SMAN 1 Lawang. Data were collected via questionnaires and analyzed using quantitative descriptive analysis. The validation results indicate high approval rates: 93% from material experts, 97% from media experts, 74% from linguists, and 92% from the Geography teacher, all rated as